Pregnant Women Kesti: Assistance Program "Pregnant Women Know Stunting" as an Effort to Prevent Stunting and Accidents in Bandengan, Pekalongan City - Ardiana Priharwanti; Andung Maheswara; Dewi Nugraheni (Indonesian Journal of Society Development, 2023)
The prevalence of stunted growth among toddlers in Indonesia is a significant factor contributing to its fifth-place ranking globally, with 38% of the total number of toddlers affected by this condition. The prevalence of stunting in Pekalongan City remains considerably high, as evidenced by the recorded figure of 1,421 under-five children who were found to be stunted during the year 2021. The 1000 HPK program is an initiative aimed at preventing stunts. This 1000-day window presents an opportunity to prioritize the nutritional status, health, and psychosocial stimulation of the child during the prenatal, breastfeeding, and complementary feeding stages. The mother's involvement is crucial, as is the role of the husband or other close family members. The Bandengan sub-district region is pertinent in the context of stunting prevention, a chronic nutritional issue that arises from prolonged insufficient nutrient intake, leading to growth impairments in children, specifically a below-average height or dwarfism relative to their age standard. Support is provided through educational interventions aimed at identifying growth and development, nutritional education for expectant mothers, physical exercises, and educational strategies for expectant mothers who are breastfeeding. The outcomes of the mentoring program entail the execution of counseling sessions aimed at enhancing awareness and comprehension of maternal health and balanced nutrition during pregnancy. The objective is to emphasize the significance of fulfilling a healthy and balanced diet to prevent early childhood stunting among pregnant women